Intra and inter-rater reliability study of pelvic floor muscle dynamometric measurements - Martinho,Natalia M. (2015)
OBJECTIVE: The aim of this study was to evaluate the intra and inter-rater reliability of pelvic floor muscle (PFM) dynamometric measurements for maximum and average strengths, as well as endurance. METHOD: A convenience sample of 18 nulliparous women, without any urogynecological complaints, aged between 19 and 31 (mean age of 25.4±3.9) participated in this study. They were evaluated using a pelvic floor dynamometer based on load cell technology. The dynamometric evaluations were repeated in three successive sessions: two on the same day with a rest period of 30 minutes between them, and the third on the following day. All participants were evaluated twice in each session; first by examiner 1 followed by examiner 2. The vaginal dynamometry data were analyzed using three parameters: maximum strength, average strength, and endurance. The Intraclass Correlation Coefficient (ICC) was applied to estimate the PFM dynamometric measurement reliability, considering a good level as being above 0.75. RESULTS: The intra and inter-raters' analyses showed good reliability for maximum strength (ICCintra-rater1=0.96, ICCintra-rater2=0.95, and ICCinter-rater=0.96), average strength (ICCintra-rater1=0.96, ICCintra-rater2=0.94, and ICCinter-rater=0.97), and endurance (ICCintra-rater1=0.88, ICCintra-rater2=0.86, and ICCinter-rater=0.92) dynamometric measurements. CONCLUSIONS: The PFM dynamometric measurements showed good intra- and inter-rater reliability for maximum strength, average strength and endurance, which demonstrates that this is a reliable device that can be used in clinical practice.